Penetrant-induced plasticization phenomenon in glassy polymers for gas separation membrane - Ismail, A. F.; Lorna, W. (Elsevier Science B.V., 2002)
Penetrant-induced plasticization of gas separation membranes has been the subject of a number of recent investigations. The plasticization of the polymer matrix by penetrant gases can be attributed to the swelling stresses on the polymer network. It is well known that sorption of carbon dioxide in glassy polymers can facilitate the local segmental organization with a reduction in the permselectivity and substantially affect membrane morphological performance. Hence, plasticization is a phenomenon that most frequently encountered in polymerâ€“gas systems for commercial CO2/CH4 separation applications where the membranes are exposed to high CO2 concentration in the feed stream. This paper attempts to present an overview of the plasticization phenomenon and the alteration of physical properties resulting from the polymer plasticization by the sorbed penetrant molecules. The plasticization suppression methods in polymeric membrane for gas separation and the future direction of research in this area are also given. Â© 2002 Elsevier Science B.V. All rights reserved.